Proceedings of the Twentieth Annual ACM-SIAM Symposium on Discrete Algorithms 2009
DOI: 10.1137/1.9781611973068.112
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Laplace Operator from Point Clouds in ℝd

Abstract: We present an algorithm for approximating the LaplaceBeltrami operator from an arbitrary point cloud obtained from a k-dimensional manifold embedded in the ddimensional space. We show that this PCD Laplace (PointCloud Data Laplace) operator converges to the LaplaceBeltrami operator on the underlying manifold as the point cloud becomes denser. Unlike the previous work, we do not assume that the data samples are independent identically distributed from a probability distribution and do not require a global mesh.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
155
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(155 citation statements)
references
References 21 publications
0
155
0
Order By: Relevance
“…Lemma 5 (e.g., [8]) Assume M is a submanifold isometrically embedded in R d with reach σ > 0. For any two x, y on M with |x − y| ≤ σ /2,…”
Section: Proof Of Propositionmentioning
confidence: 99%
“…Lemma 5 (e.g., [8]) Assume M is a submanifold isometrically embedded in R d with reach σ > 0. For any two x, y on M with |x − y| ≤ σ /2,…”
Section: Proof Of Propositionmentioning
confidence: 99%
“…Gaussian kernel weights have been advocated by Belkin et al [1] as providing good properties such as convergence to the continuous Laplace-Beltrami operator. Interestingly, the above weights correspond to a spectral decomposition where the original manifold M is considered in a higher dimensional space R 3+l where l is the dimension of the co-domain of F , e.g.…”
Section: Computational Strategymentioning
confidence: 99%
“…Several discrete Laplace operators have been developed to compute a Laplace-like operator either from a mesh approximating the hidden manifold [5,10,16], or more generally, simply from a set of points sampled from a hidden manifold [1,6]. For high dimensional data, the most practical and also most popular discrete Laplace operator is perhaps the weighted graph Laplace operator -the reason being its simplicity and practicality.…”
Section: Introductionmentioning
confidence: 99%
“…For high dimensional data, the most practical and also most popular discrete Laplace operator is perhaps the weighted graph Laplace operator -the reason being its simplicity and practicality. To compute it, one only needs to build the proximity graph from the input points, while other operators require a mesh structure either locally [6] or globally [5,10,16], which is expensive for high dimensional data. Furthermore, Belkin and Niyogi showed that, for points uniformly randomly sampled from the hidden manifold, the Gaussian-weighted graph Laplacian converges to the manifold Laplacian both pointwise [4] and in spectrum [3].…”
Section: Introductionmentioning
confidence: 99%